Sistem Informasi Data Arsip Peta Berbasis Website Pada Dinas Perpustakaan Dan Arsip Daerah Provinsi Jambi - Moh Yusuf; Dwi Pebri Ratmiyanti; Muhammad Al-Fajri; Muhammad Saif Akbar; Nissa Hassanah Siagian; Muhammad Hafid Bangko; Yundria Rahmadani; Wafiq Fadiyah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) - Institut Teknologi dan Bisnis Semarang, 2024)
The map archiving system in the Jambi Province DPAD is currently facing quite serious challenges because it still relies on manual recording methods. This reliance on manual recording has caused the process of searching for map archive data to be slow and inefficient. Employees have to spend quite a long time searching for and managing the necessary information, resulting in disruptions in productivity and a high potential for data errors. To address this issue, we designed a solution that we believe can provide significant improvements in the management of map archive data. This project is in the form of designing a Website-Based Map Archive Data Information System which will replace the existing manual method. By using web-based technology, this system is specifically designed to increase efficiency and accuracy in managing map archives. It is hoped that with the implementation of this system, the data search and management process will become faster, easier and more structured, thereby helping to increase productivity and reduce the risk of errors in information management.